The impact of the Asian chestnut gall wasp (Dryocosmus kuriphilus) on chestnut tree growth may be mediated by site resources - Castedo-Dorado, Fernando; Álvarez-Álvarez, Pedro; Lombardero, María Josefa (Frontiers in Forests and Global Change, 2023)
Introduction The Asian chestnut gall wasp (Dryocosmus kuriphilus) is a major pest of chestnut trees worldwide, seriously affecting chestnut cultivation. Information concerning the effects of gall wasp attack on diameter growth of chestnut trees is currently scarce and limited to coppice stands and to use of the growth of a non-target control species (unaffected by the pest) for reference purposes. The effects of the pest on widely-spaced plantations (grown at a much lower density than chestnut coppices) and the use of explicitly-observed annual infestation rate data remain to be explored. Methods In the present study, we analyzed the impact of the chestnut gall wasp on the diameter growth of chestnut trees, using data from 16 experimental plots established in widely-spaced plantations located in good quality sites. Two of the plots are in plantations where a susceptible hybrid chestnut clone and a chestnut clone resistant to the gall wasp coexist, whereas the remaining 14 plots are in Castanea sativa plantations where the level of gall wasp infestation varies across trees and years. The plots were surveyed to determine the diameter growth of the trees and the level of infestation during 5 years (2017–2021). Results The infestation level corresponding to the theoretical damage threshold was surpassed inmost plots during the study period. Nevertheless, there were no differences in the growth of attacked and unaffected plants in the two plots planted with hybrid clones with contrasting susceptibility to the gall wasp. The attack had a modest effect in C. sativa plots, with a mean reduction in annual basal area increment of 9.9%. Discussion These findings apparently contradict previous reports of a marked reduction in radial growth of chestnut coppice trees due to gall wasp attack. The difference in findings may be related to increased compensation for herbivory with increasing levels of resources (especially light) in the plantations under study, which were less dense than previously studied stands. The study outcomes add to existing knowledge on the impact of chestnut gall wasp on wood formation and may have implications regarding planting site recommendations and subsequent stand management.